2019
DOI: 10.1002/ccd.28509
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐related difference in the use of percutaneous left ventricular assist device in patients undergoing complex high‐risk percutaneous coronary intervention: Insight from the cVAD registry

Abstract: Objective To assess the in‐hospital and short‐term outcome differences between males and females who underwent high‐risk PCI with mechanical circulatory support (MCS). Background Sex differences have been noted in several percutaneous coronary intervention (PCI) series with females less likely to be referred for PCI due increased risk of adverse events. However, data on sex differences in utilization and outcomes of high‐risk PCI with MCS is scarce. Methods Using the cVAD Registry, we identified 1,053 high‐ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Transfusion rates in the four studies in which the majority of transfusions were stated as being performed in the setting of baseline anaemia ranged from 5.0% to 34.3%. 12,23,26,32 Few studies included in our review reported on haemolysis (9 of 23 studies). Of these, 3 studies reported 0% haemolysis rates, 1…”
Section: Transfusion Ratesmentioning
confidence: 99%
See 3 more Smart Citations
“…Transfusion rates in the four studies in which the majority of transfusions were stated as being performed in the setting of baseline anaemia ranged from 5.0% to 34.3%. 12,23,26,32 Few studies included in our review reported on haemolysis (9 of 23 studies). Of these, 3 studies reported 0% haemolysis rates, 1…”
Section: Transfusion Ratesmentioning
confidence: 99%
“…Bleeding complications over time demonstrated that the variability in bleeding risk seen across centres has not changed meaningfully over the last 15 years (Figure 1). 7,[11][12][13][14][15][16][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Given the broad scope of bleeding complications (comprising both access and non-access-related bleeding during PCI), often complicated by pre-existing anaemia and the inclusion of some urgent HR-PCI patient populations, this variability is not surprising. Likewise, many series reported relatively low numbers of cases over extended time periods, suggesting that any advantages of increased operator skill, using best practices accrued through increasing experience, could not be ascertained.…”
Section: Trends In Bleeding and Vascular Complications Over Timementioning
confidence: 99%
See 2 more Smart Citations
“…15 It is unclear if similar disparities exist in the clinical profile and outcomes of men and women receiving temporary MCS for AMI-CS in the United States. [16][17][18] In light of these conflicting data, this study sought to assess sex differences in the use and outcomes of MCS in a 12-year nationally representative AMI-CS population. We hypothesized that women would receive MCS less frequently and have higher in-hospital mortality compared with men.…”
mentioning
confidence: 99%